Assessing Sustainable Food Security in the Central Maghreb through Aggregated Indicators - Soler, José; Arroyo, Juan Manuel (UNISCI Discussion Papers, 2014)
An aggregated indicator has been developed using the multivariate statistical tool of principal components analysis, with a matrix of 60 countries x 21 variables. Central Maghreb countries don’t show sustainable food security within the countries and variables included in this study. Although food production shows a relatively environmental sustainability, the social and productive dimensions are relatively unsustainable because cereals represent a great amount of energy in diets but optimum dietary requirements and not properly fulfilled and cereal production and yields in these countries are low and quite variable, so they depend on external imports.
Keywords: Aggregated Indicators; Central Maghreb; Food Security.